Fetal Meconium Peritonitis – Prenatal Findings and Postnatal Outcome: A Case Series, Systematic Review, and Meta-Analysis - Shinar, Shiri; Agrawal, Swati; Ryu, Michelle; Van Mieghem, Tim; Daneman, Alan; Ryan, Greg; Zani, Augusto; Chiu, Priscilla; Chitayat, David (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To describe the postnatal outcome of fetal meconium peritonitis and identify prenatal predictors of neonatal surgery.Methods We retrospectively reviewed all fetuses with ultrasound findings suspicious for meconium peritonitis at a single center over a 10-year period. A systematic review and meta-analysis were then performed pooling our results with previous studies assessing prenatally diagnosed meconium peritonitis and postnatal outcome. Prenatal sonographic findings were analyzed to identify predictors for postnatal surgery.Results 34 cases suggestive of meconium peritonitis were diagnosed at our center. These were pooled with cases from 14 other studies yielding a total of 244 cases. Postnatal abdominal surgery was required in two thirds of case (66.5 %). The strongest predictor of neonatal surgery was meconium pseudocyst (OR [95 % CI] 6.75 [2.53–18.01]), followed by bowel dilation (OR [95 % CI] 4.17 [1.93–9.05]) and ascites (OR [95 % CI] 2.57 [1.07–5.24]). The most common cause of intestinal perforation and meconium peritonitis, found in 52.2 % of the cases, was small bowel atresia. Cystic fibrosis was diagnosed in 9.8 % of cases. Short-term neonatal outcomes were favorable, with a post-operative mortality rate of 8.1 % and a survival rate of 100 % in neonates not requiring surgery.Conclusion Meconium pseudocysts, bowel dilation, and ascites are prenatal predictors of neonatal surgery in cases of meconium peritonitis. Fetuses with these findings should be delivered in centers with pediatric surgery services. Though the prognosis is favorable, cystic fibrosis complicates postnatal outcomes.
Keywords: meconium peritonitis; pseudocyst; surgery; predictor; cystic fibrosis